Invasive solid papillary carcinoma with neuroendocrine differentiation of the breast: a case report and literature review - Xue Lin; Yoshiaki Matsumoto; Tomomi Nakakimura; Kazuo Ono; Shigeaki Umeoka; Masae Torii; Hiroshi Yoshibayashi; Masakazu Toi (Surgical Case Reports, 2020)
Abstract Background Solid papillary carcinoma (SPC) of the breast is a rare breast cancer that accounts for less than 1% of all breast cancers. The optimal clinical management of SPC remains controversial. Here, we report a case of invasive SPC with neuroendocrine differentiation in addition to review of the current literature. Case presentation A premenopausal 46-year-old female presented with a mass in her left breast that tended to increase in size over a 10-month period. Mammography and ultrasonography revealed a mass in the left upper-inner quadrant. The resulting images suggested a category 3 breast tumor according to the Breast Imaging Reporting and Data System (BI-RADS). A core needle biopsy (CNB) was performed, and the pathological findings showed a solid papillary pattern and atypical cells suggestive of noninvasive SPC. After a left partial mastectomy and sentinel lymph node biopsy (SLNB), the specimens were sent for histopathological analysis for further investigation. Postoperative pathological findings suggested invasive SPC. Whole-breast radiation therapy and adjuvant hormonal therapy were performed as postoperative treatments. Three years after surgery, multiple lung metastases were detected, and the patient was treated with a gonadotropin-releasing hormone agonist and an aromatase inhibitor. Five months later, multiple liver metastases and bone metastases appeared, and oral 5-fluorouracil was chosen for the subsequent treatment. The patient has been treated for 5 years to date, and she is continuing to take oral 5-fluorouracil and is alive without any further disease progression. Conclusions We report a rare case of premenopausal invasive SPC with multiple metastases. Further study is needed to clarify the molecular characteristics and clinical behaviors of SPC and to explore the optimal treatment strategy.